A point mutation in the HIV-1 Tat responsive element is associated with postintegration latency. - Emiliani, S (1996)
Study of the mechanism of HIV-1 postintegration latency in the ACH2 cell line demonstrates that these cells failed to increase HIV-1 production following treatment with exogenous Tat. Reasoning that the defect in ACH2 cells involves the Tat response, we analyzed the sequence of tat cDNA and Tat responsive element (TAR) from the virus integrated in ACH2. Tat cDNA sequence is closely related to that of HIV LAI, and the encoded protein is fully functional in terms of long terminal repeat (LTR) transactivation. Cloning of a region corresponding to the 5'-LTR from ACH2, however, identified a point mutation (C37 -> T) in TAR. This mutation impaired Tat responsiveness of the LTR in transient transfection assays, and the measured defect was complemented in cells that had been treated with tetradecanoyl phorbol acetate or tumor necrosis factor type alpha (TNF-alpha). A compensatory mutation in TAR (G28 -> A), designed to reestablish base pairing in the TAR hairpin, restored wild-type Tat responsiveness. When the (C37 -> T) mutation was introduced in an infectious clone of HIV-1, no viral production was measured in the absence of TNF-alpha, whereas full complementation was observed when the infection was conducted in the presence of TNF-alpha or when a compensatory mutation (G28 -> A) was introduced into TAR. These experiments identify a novel mutation associated with HIV-1 latency and suggest that alterations in the Tat-TAR axis can be a crucial determinant of the latent phenotype in infected individuals.